A novel approach for intrusion detection in mobile ad hoc networks. (29th October 2019) - Chaudhari, Bhushan S.; Prasad, Rajesh S.
Mobile ad hoc network (MANET) consists of various nodes and they interact with each other cooperatively. However, the cooperative nature of MANET provides a gateway for intruders to interrupt the communication. Two types of approaches have been proposed for the IDS in the literature. The first approach has been used for the improvement in the conventional models and the second approach based on the unconventional models. Our focus is on the unconventional methods since they perform better in the diversified environment. A number of unconventional methods viz. Watchdog, EAACK, etc. have been discussed in the literature. However, intrusion detection model based on particle swarm optimization (PSO) for distributed and advanced attacks have not been discussed yet. In this paper, we proposed a novel approach based on PSO for the IDS in MANET. The proposed model is compared with existing models like Watchdog and EAACK. Comprehensive objective function in the evaluation of node trustworthiness is a key point of this model.